SEMIOTIC SIGNS IN THE NOVEL “PERCY JACKSON & THE OLYMPIANS: THE LIGHTNING THIEF” BY RICK RIORDAN - Kartika, Lia; Burhamzah, Muftihaturrahmah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
The purpose of this study, which focused on the novel Percy Jackson & the Olympians: the lightning thief by Rick Riordan, was to examine the many types of signs used in the novel that focused on the object, namely icon, index, and symbol it contains. This study used a descriptive qualitative methodology and Pierce's semiotic theory as its theoretical framework. Using note-taking as the primary research instrument, the data for this study were gathered from the novel Percy Jackson & the Olympians: the lightning thief by Rick Riordan. The analysis's results showed that Pierce's semiotic theory can be used to understand the meaning of these three sign components, especially as it relates to the relationship between their object, representamen, and interpretant. For example, the visual of big marble frieze in the novel is the icon of Greek gods; the blood that comes out is an index of a scar; and a black-and-white bull’s horn is a symbol of Minotour.